Capital Flows, Turbulences, and Distribution: The Case of Turkey - Özlem Onaran (Intervention. Zeitschrift fuer Ökonomie / Journal of Economics, 2007)
This paper presents the mechanism of the boom-bust cycles in the context of domestic and international financial liberalisation in the developing countries, and the effects of crises and exchange rate volatility on functional income distribution. It is based on the case of Turkey, which has experienced two severe crises in 1994 and 2001 after the liberalisation of capital flows, and which has also been hit the hardest during the May-June 2006 turbulences. The paper analyses the recent turbulences in the global economy and their consequences in the emerging markets as a case study to illustrate the endogenous formation of expectations. The recovery in Turkey after the turmoil is not based on a solution to the structural causes of the problem, since it has completely depended on the reversal of the capital outflows thanks to high interest rate, but the continuity of this game is far from clear.
Keywords: E12; E22; E25; F32; G32; 330; financial fragility; boom-bust cycles; post-Keynesian; distribution; Turkey